# Solve for x. log(base 5)(x + 22) - log(base 5)(x - 2) = 2 If there are multiple answers, separate with a comma.

*print*Print*list*Cite

In order to solve `log_(5)(x+22) - log_(5)(x - 2) = 2`

we will use one of the properties of logarithms:

`log_(b)x - log_(b)y = log_(b)(x/y)`

Therefore we will have:

`log_(5)(x+22) - log_(5)(x - 2) = 2 rArr log_(5) ( x+22 ) / ( x-2 ) = 2`

Using the meaning of logs, this equation equals:

`5^2 = ( x+22 ) / ( x - 2 )` `rArr` `25 = ( x+22 ) / ( x - 2 )` We will now multiply both sides by ( x - 2) to get:

`25 ( x - 2 ) = x + 22` Distribute the 25.

`25x - 50 = x + 22` Subtract x from both sides.

`24x - 50 = 22` Add 50 to both sides.

`24x = 72` Divide both sides by 24.

**The final answer is `x = 3.` **

The equation `log_5(x + 22) - log_5(x - 2) = 2` has to be solved for x.

`log_5(x + 22) - log_5(x - 2) = 2`

= `log_5((x+22)/(x - 2)) = 2`

=> `(x+22)/(x - 2) = 5^2`

=> `(x+22)/(x - 2) = 25`

=> x + 22 = 25x - 50

=> 24x = 72

=> x = 3

**The solution of the equation is x = 3**